2012
DOI: 10.3390/molecules170910446
|View full text |Cite
|
Sign up to set email alerts
|

Simple Synthesis of Modafinil Derivatives and Their Anti-inflammatory Activity

Abstract: Simple synthesis of modafinil derivatives and their biological activity are described. The key synthetic strategies involve substitution and coupling reactions. We determined the anti-inflammatory effects of modafinil derivatives in cultured BV2 cells by measuring the inhibition of nitrite production and expression of iNOS and COX-2 after LPS stimulation. It was found that for sulfide analogues introduction of aliphatic groups on the amide part (compounds 11a–d) resulted in lower anti-inflammatory activity com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…However, several other drugs with anti-inflammatory properties may additional yield antidepressant treatment effects. Statins [ 52 ], poly-unsatturated fatty acids [ 53 ], pioglitazone [ 54 ], corticosteroids, minocycline [ 55 ], and modafinil [ 56 ] have anti-inflammatory properties and studies have associated these drugs with potential antidepressant treatment effects.…”
Section: Review Of Anti-inflammatory Agents and Potential Antidepressmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several other drugs with anti-inflammatory properties may additional yield antidepressant treatment effects. Statins [ 52 ], poly-unsatturated fatty acids [ 53 ], pioglitazone [ 54 ], corticosteroids, minocycline [ 55 ], and modafinil [ 56 ] have anti-inflammatory properties and studies have associated these drugs with potential antidepressant treatment effects.…”
Section: Review Of Anti-inflammatory Agents and Potential Antidepressmentioning
confidence: 99%
“…Finally, another emerging drug is the anti-epileptic drug modafinil, which has been associated with anti-inflammatory properties [ 56 ] and furthermore shown effective antidepressant effects in augmentation strategies for acute depressive episodes, including symptoms of fatigue, in both unipolar and bipolar disorders [ 67 , 68 ]. However, due to several side effects, cautious use of modafinil is recommended [ 69 ].…”
Section: Review Of Anti-inflammatory Agents and Potential Antidepressmentioning
confidence: 99%
“…Modafinil is a novel anti-epileptic and wakefulness-promoting drug, which has also been associated with anti-inflammatory properties [ 210 ]. There are several studies that demonstrated the beneficial effects of modafinil on depression-like behavior in both animal models and clinical trials (Table 2 ).…”
Section: Effects Of Anti-inflammatory Drugs On Depressive Symptomsmentioning
confidence: 99%
“…Besides, modafinil derivatives exert anti-inflammatory effects much better than aspirin via decreasing iNOS and COX-2 in LPS-treated BV2 microglia cells. Modafinil can also inhibit the apoptosis and autophagy in rapamycin-induced hippocampal neuronal cells (Jung et al 2012). Furthermore, the systematic review indicates the procognitive effects of modafinil on major depressive disorder (Cao et al 2019).…”
Section: Introductionmentioning
confidence: 98%